2021
DOI: 10.1159/000518691
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Sleep in Promoting a Healthy Body Composition: Underlying Mechanisms Determining Muscle, Fat, and Bone Mass and Their Association with Sleep

Abstract: Sleep plays an essential role in human life. While sleep is a state elicited by the brain, its vital role reaches beyond maintaining brain health. Unhealthy sleeping habits have been associated with increased risk for inflammation, obesity, or diabetes. Evidence is emerging that sleep guides processes playing an important role in promoting the regulation of endocrine function involved in tissue regeneration and tissue remodelling. Thereby, sleep presumably is a critical factor contributing to the balance of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 363 publications
0
19
0
Order By: Relevance
“…Sleep represents a powerful system for promoting brain and body health. It is suggested to play a role in a plethora of functions such as cleaning away toxic by-products [1][2][3], synaptic homeostasis [4], memory consolidation [5][6][7][8][9][10][11], metabolic [12], and cardiovascular functions [13][14][15][16], and body core tissue turnover [17]. Particularly, nonrapid eye movement (NREM) sleep with its large-amplitude, low-frequency slow waves has been proposed to guide those beneficial effects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep represents a powerful system for promoting brain and body health. It is suggested to play a role in a plethora of functions such as cleaning away toxic by-products [1][2][3], synaptic homeostasis [4], memory consolidation [5][6][7][8][9][10][11], metabolic [12], and cardiovascular functions [13][14][15][16], and body core tissue turnover [17]. Particularly, nonrapid eye movement (NREM) sleep with its large-amplitude, low-frequency slow waves has been proposed to guide those beneficial effects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to explain the reduced osteoblast differentiation and imbalance in bone turnover status, which was likely unrelated to the negligible decrease in body mass. Furthermore, if these changes were mediated by other possible effects of the SD, such as increased inflammation 30 , 31 and vitamin D deficiency, then an increase in bone resorption would have been expected; 30 , 32 however, this was not observed. Our finding of marked alterations in transcriptome of bone tissue shows that the SD directly acts on osteocytes rather than via central nervous system function and further suggests that sleep may play an equally important role in peripheral energy metabolism, as previous reported.…”
Section: Discussionmentioning
confidence: 99%
“…178,179 Sleep restriction also results in the loss of the beneficial effects of GH on muscle mass and fat distribution. 180 Sleep debt is also associated with an increased prediction towards the consumption of high-fat or carbohydrate-rich foods as well as reduced physical activity, 181 as a result of the aforementioned endocrine changes 181 and enhanced activation of brain reward and foodsensitive centres in response to unhealthy food. 182…”
Section: Emerging Endocrine Disruptors and Additional Factorsmentioning
confidence: 99%
“…153 Studies evaluating T2DM risk in MHO identified an approximate 4-fold increased risk compared with MHNW. 179,180,197,212,213,227 Subjects who progressed to MUHO were at higher risk for developing T2DM compared to those who retained the MHO status, yet this risk was lower when compared to those with stable MUHO. 228 On the other hand, Wang et al reported that individuals with persistent MHO were not at increased risk compared with stable MHNW after 6 years of follow-up 229 but with very wide 95% confidence intervals in the odds ratio (0.20-1.40).…”
Section: Zhang Et Al Reported the Highest Transitions From Muhnw Tomentioning
confidence: 99%